2016
DOI: 10.4137/rpo.s34816
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness and Efficiency of Inpatient Rehabilitation Services in Thailand: A Prospective Multicenter Study

Abstract: OBJECTIVE:To investigate the effectiveness and efficiency of inpatient rehabilitation. METHODS: A total of 2,081 patients across 14 hospitals were recruited in this prospective, multicenter cohort study. Data on the diagnoses, types of admission, length of stay (LOS), and functional ability score based on a modified Barthel index (BI) at admission (BIa) and at discharge (BId) were collected. Effectiveness was defined as the difference of BI (ΔBI) and efficiency as ΔBI divided by LOS. RESULTS: The majority of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…This outcome may due to some of our patients not being ready to undertake a rehabilitation program (nonintensive goal of admission of 42.0%), and approximately 30% had complications during the rehabilitation period. 3 Moreover, almost 50% of our subjects were SCI, which is associated with complicated physical disabilities, including motor impairment, di culty with urination and defecation, and sexual dysfunction, that can adversely impact QoL [17], and some self-evaluated themselves as having poor QoL [18][19][20].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This outcome may due to some of our patients not being ready to undertake a rehabilitation program (nonintensive goal of admission of 42.0%), and approximately 30% had complications during the rehabilitation period. 3 Moreover, almost 50% of our subjects were SCI, which is associated with complicated physical disabilities, including motor impairment, di culty with urination and defecation, and sexual dysfunction, that can adversely impact QoL [17], and some self-evaluated themselves as having poor QoL [18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…Ploypetch and Dajpratham reported improved QoL after rehabilitation in patients admitted for intensive rehabilitation [16]. In 2016, Kuptniratsaikul, et al conducted a multicenter study in 2,081 rehabilitation inpatients that revealed the most e cient type of admission to be intensive rehabilitation, which could improve functional score better than other types of admission [3]. A 2012 study showed association between better patient QoL perceptions and the level of patient independence [23].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations